Population Health Metrics - Samet, Jonathan; Hussein, Shereen; SpringerLink (Online service) (London : BioMed Central : Imprint: BioMed Central.)
Population Health Metrics addresses issues relating to concepts, methods, ethics applications, and results in the measurement of the health of populations. This includes areas of health state measurement and valuation, summary measures of levels of population health, and inequality in population health, descriptive epidemiology at the population level, burden of disease and injury analysis, disease, and risk factor modeling for populations and comparative assessment of risks to health at population level. The journal provides a platform for population health researchers in all these areas to share their findings with the global research community.
Keywords: Public health; Epidemiology; Sociology$1 (BMethodology.s; Medical care; Public Health; Epidemiology; Sociological Methods; Health Care